Dark sector interactions and the curvature of the universe in light of Planck's 2018 data. Issue 8 (9th August 2021) - Benetti, M.; Borges, H.A.; Pigozzo, C.; Carneiro, S.; Alcaniz, J.S.
Abstract: We investigate the observational viability of a class of interacting dark energy (iDE) models in the light of the latest observations of the Cosmic Microwave Background and type Ia supernovae, and the SH0ES measurement of the current expansion rate H 0 . Our analysis explores both the assumptions of a non-zero spatial curvature and a free curvature density, the correlation between the interaction parameter α and H 0, and updates the results reported in [1]. The results show that the best-fit of our joint analysis clearly favours a positive interaction, i.e., an energy flux from dark matter to dark energy, with α≈ 0.2, while the non-interacting case, α = 0, is ruled out by more than 3σ confidence level under the flat space assumption. On the other hand, considering a non-zero spatial curvature, we find a significant anti-correlation between the interaction parameter and the universe density curvature, which seems to relax the correlation between the parameters α and H 0, as well as between H 0 and the normalization of the matter power spectrum on scales of 8 h -1 Mpc (σ8 ). Finally, we discuss the influence of considering the SH0ES prior on H 0 in the joint analyses performed, and find that such a choice does not change considerably the standard cosmology predictions but has a significant influence on the results of the iDE model.